Cultural Postmodernism and Universalism among Youth in City of Yazd - Hossein Afrasiabi; Yasin Khorrampour (Taḥqīqāt-i Farhangī-i Īrān)
Universalism in the context of information and communication technology has lead to fading of the boundaries of time and place.This process is allowed to enter a new era called postmodernism. Postmodernism has challenged modern characteristics such as reason and progress. The cultures of postmodern societies are surface and moving that is greatly influenced by media. The aim of this study is to examine the relationship between universalism and cultural postmodernism among Youth in city of Yazd. Research method was survey and sample contained 384 youth aged 16-29 in city of Yazd. Sampling method was random stratified multistageand data collected by a researcher designed questionnaire. Results showed that there is a significant relationship between universalism and cultural postmodernism. There was a significant relationship between transnational norms of universalism with other aspects of cultural postmodernism, except consumerism. Multiple regression results showed that two dimensions of universalism explain 22 percent of cultural postmodern variance.